Human Urine Derived Stem Cells in Combination with β-TCP Can Be Applied for Bone Regeneration. - Junjie Guan; Jieyuan Zhang; Haiyan Li; Zhenzhong Zhu; Shangchun Guo; Xin Niu; Yang Wang; Changqing Zhang (PLoS ONE, 2015)
Bone tissue engineering requires highly proliferative stem cells that are easy to isolate. Human urine stem cells (USCs) are abundant and can be easily harvested without using an invasive procedure. In addition, in our previous studies, USCs have been proved to be able to differentiate into osteoblasts, chondrocytes, and adipocytes. Therefore, USCs may have great potential and advantages to be applied as a cell source for tissue engineering. However, there are no published studies that describe the interactions between USCs and biomaterials and applications of USCs for bone tissue engineering. Therefore, the objective of the present study was to evaluate the interactions between USCs with a typical bone tissue engineering scaffold, beta-Tricalcium Phosphate (β-TCP), and to determine whether the USCs seeded onto β-TCP scaffold can promote bone regeneration in a segmental femoral defect of rats. Primary USCs were isolated from urine and seeded on β-TCP scaffolds. Results showed that USCs remained viable and proliferated within β-TCP. The osteogenic differentiation of USCs within the scaffolds was demonstrated by increased alkaline phosphatase activity and calcium content. Furthermore, β-TCP with adherent USCs (USCs/β-TCP) were implanted in a 6-mm critical size femoral defect of rats for 12 weeks. Bone regeneration was determined using X-ray, micro-CT, and histologic analyses. Results further demonstrated that USCs in the scaffolds could enhance new bone formation, which spanned bone defects in 5 out of 11 rats while β-TCP scaffold alone induced modest bone formation. The current study indicated that the USCs can be used as a cell source for bone tissue engineering as they are compatible with bone tissue engineering scaffolds and can stimulate the regeneration of bone in a critical size bone defect.